Behavioral Health Parity and the Affordable Care Act - Frank, Richard G. (J Soc Work Disabil Rehabil, 2014)
Prior to the passage of the Mental Health Parity and Addiction Equity Act (MHPAEA) and the ACA, about 49 million Americans were uninsured. Among those with employer sponsored health insurance, 2 % had coverage that entirely excluded mental health benefits and 7% had coverage that entirely excluded substance use benefits. The rates of non-coverage for mental and substance use disorder care in the individual health insurance markets are considerably higher. Private health insurance generally limits the extent of these benefits. The combination of MHPEA and ACA extended overall health insurance coverage to more people and expanded the scope of coverage to include mental health and substance abuse benefits.